Funkcja dźwigni operacyjnej w anlizie zmian zysku - Mielcarek, Jarosław (Function of the Operating Leverage in the Profit Variations Analysis, 2006)
Presented formulas for the critical rate of variable cost growth and the point of constant profit were expressed with the use of profit growth rates for price changes and fixed costs, and the variable cost operating leverage. Both formulas have analytical form in such a sense that they are defined by the operating leverages of additive factors, i.e. prices, variable and fixed costs, resulting from the initial conditions and price and fixed costs growth rates. The graphic interpretation of changes in the financial situation of the company under the influence of changes in the levels of additive factors was made with the use of the family of demand operating leverage functions. The function of the profit growth rate was formulated as a linear function of variable cost growth rate. Its slope coefficient is defined by the variable cost operating leverage, and the intercept is equal to profit growth rate for the price and fixed costs changes. The defining of variable costs growth rates for the characteristic points of this function, such as critical condition of the variable cost growth rate or point of constant profit, enable the explanation of changes occurring in the profit level and the demand operating leverage under the influence of additive factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 273-283